ANALISIS KINERJA KEUANGAN DITINJAU DARI LIKUIDITAS DAN RENTABILITAS PADA PT. BANK PERKREDITAN RAKYAT SAPTACRISTY UTAMA, PENDAHULUAN Salah satu perusahaan yang menjual jasa adalah perusahaan yang bergerak dalam bidang perbankan atau lebih dikenal dengan - Putri Anggreni (Forum Manajemen, 2012)
The Intention of this research is to know level of likuiditas rentabilityand, its effectiveness and also growth of monetary performance which evaluatedfrom the level of likuiditas (cash ratio and loan to deposit ratio) and rentability(return on asset and of return on equity). The Analyzer which is used in this researchis monetary ratio analysis and statistical analysis. Statistical analysis which is usedis determination of historical standard with searching standard and mean of deviasifrom result of financial analysis, so that can assess effectiveness level and also itsgrowth. The analysis result which have done,showing that is monetary performance which is have a fluctuation. Likudity ratio analysis ratio and also adapted with historical standard pursuant to cash ratio,shows that the percentage in the 2009cash ratio equal to 14% (enough liquid), year 2010 going down to become 13,82%(enough liquid) and for year 2011 mounting to become 22% (liquid). For Loan ofdeposit ratio, in 2009 shows 79,27% number (enough liquid), mounting year 2010becoming 84,93% (enough liquid), while year 2011 going down to become 64,95%(less liquid). Rentability ratio is and also adapted for by historical standard, evaluatedfrom return n asset have effectiveness level which is have fluctuation, in 2009 assetson return equal to - 0,41 (efficient enough), mounting for 2010 becoming 1,98%(efficient enough), so also for 2011 equal to 4,46 is% (efficient). Rentability pursuantto return to equity have effectiveness level which is have fluctuation. in 2009 return onequity equal to - 3,89% (less efficient), mounting in 2010 becoming 11,26% (efficientenough), so also for 2011 becoming 18,85% (efficient enough). The suggestionwhich can be suggested to the BPR to be more improve asset of management andoptimise credit giving to society so that it can happened the increasing of profitcredit earnings at BPR, without disregarding observation to giving credit procespass through 5C application (character, capacity, capital, condition, collateral) toclient candidate.